Implementing evidence-based practice: the challenge of delivering what works for people with learning disabilities at risk of behaviours that challenge. Issue 3 (11th November 2020) - Denne, Louise D.; Gore, Nick J.; Hughes, J. Carl; Toogood, Sandy; Jones, Edwin; Brown, Freddy Jackson
Abstract : Purpose: There is an apparent disconnect between the understanding of best practice and service delivery in the support of people with learning disabilities at risk of behaviours that challenge. We suggest, is a problem of implementation. The purpose of this paper is to explore reasons why this might be the case: a failure to recognise the collective works of successive generations of research and practice; and a failure to address the macro-systems involved and systems changes needed to support implementation. Design/methodology/approach: This paper reviews the consensus that exists in respect of best practice. Drawing upon ideas from implementation science the paper highlights the complexities involved in the implementation of all evidence-based practices and uses this as a framework to propose ways in which an infrastructure that facilitates the delivery of services in the learning disabilities field might be built. Findings: This paper highlights core recommended practices that have been consistent over time and across sources and identifies the systems involved in the implementation process. This paper demonstrates that many of the necessary building blocks of implementation already exist and suggests areas that are yet to be addressed. Critically, the paper highlights the importance of, and the part that all systems need to play in the process. Originality/value: In the absence of any generalised implementation frameworks of evidence-based practice in the learning disabilities field, the paper suggests that the findings may provide the basis for understanding how the gap that exists between best practice and service delivery in the support of people with a learning disability at risk of behaviours that challenge might be closed.